2022
DOI: 10.1038/s41416-022-01832-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors alone vs immune checkpoint inhibitors—combined chemotherapy for NSCLC patients with high PD-L1 expression: a network meta-analysis

Abstract: Background We indirectly compared the effects of immune checkpoint inhibitors alone (ICI) and ICI-combined chemotherapy (chemo-ICI) in patients with non-small cell lung cancer who had high programmed death-ligand 1 (PD-L1) expression (defined as tumour proportion score ≥50% or TC3/IC3) through network meta-analyses. Methods Through literature searches, we shortlisted 22 randomised controlled trials encompassing 4289 patients, with objective response rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
0
21
2
Order By: Relevance
“…We used the ASCO and ESMO clinical benefit frameworks to guide our interpretation of whether changes in survival were clinically meaningful. In a secondary analysis, we evaluated patterns of ICI use with and without concomitant chemotherapy because evidence has suggested superiority of ICIs in combination with chemotherapy in some settings …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the ASCO and ESMO clinical benefit frameworks to guide our interpretation of whether changes in survival were clinically meaningful. In a secondary analysis, we evaluated patterns of ICI use with and without concomitant chemotherapy because evidence has suggested superiority of ICIs in combination with chemotherapy in some settings …”
Section: Introductionmentioning
confidence: 99%
“…In a secondary analysis, we evaluated patterns of ICI use with and without concomitant chemotherapy because evidence has suggested superiority of ICIs in combination with chemotherapy in some settings. [24][25][26][27][28]…”
mentioning
confidence: 99%
“…Studies show when immunotherapies are included in treatment regimens, patients with NSCLC experience prolonged overall survival and more patients achieve complete responses [13, 14]. Additionally, therapies which are targeted at specific genetic mutations are leading to longer progression-free survival [6, 15, 16]. With more durable and targeted therapeutic regimens, a patient’s second primary lung cancer is given more time and thus more opportunity to grow, to mutate, and to unmask itself.…”
Section: Discussionmentioning
confidence: 99%
“…Several published NMAs have considered populations with different levels of PD-L1 expression l as potential subgroups ( 16 , 53 , 57 , 62 ). For example, Liu et al ( 16 ) reported that the greatest OS was achieved by niv + ipi + che in patients with PD-L1 expression< 1% and by pem + che in patients with PD-L1 expression ≥ 1%.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al ( 16 ) reported that the greatest OS was achieved by niv + ipi + che in patients with PD-L1 expression< 1% and by pem + che in patients with PD-L1 expression ≥ 1%. Sheng et al ( 53 ) and Wang et al ( 62 ) found that, among nsq-NSCLC patients with high PD-L1 expression, ICI combination therapies were associated with significantly greater OS and PFS benefits than ICI-free therapies, but significant PFS benefits only when compared with ICIs alone therapy ( 53 , 62 ). However, Passiglia et al ( 57 ) found that ICI combinations had limited effects in patients with high PD-L1 expression, but might be a suitable option for the subgroup who are PD-L1 negative.…”
Section: Discussionmentioning
confidence: 99%